SISTEM INFORMASI PEMESANAN TIKET PADA PO TRANEX GRAHA MANDIRI PADANG: EMPLOYEE PAYROLL INFORMATION SYSTEM AT DENTACIIDENTAL CLINIC PADANG - Jusmita Weriza; Guntur Wirawan (JENTIK, 2024)
The design of this system aims to produce a web-based employee payroll data processing information system and produce applications that can be implemented at the Detancio Dental Clinic.The design of this system was built using a website platform and run online. The research method uses the System Development Life Cycle (SDLC) with the Waterfall model approach which consists of 5 stages, namely, a) Analysis b) Design c) Implementation d) Maintenance e) Planning. The programming language used is (PHP), and the database application uses a data processor (MySql) as the database (RDBMS). The system design tool uses the UML (Unified Modeling Language) method using 4 (four) diagrams according to design needs, namely Use Case Diagrams, Activity Diagrams, Class Diagrams, and Sequence Diagrams.This web-based Employee Payroll Information System makes it easier for clinical staff to process salary data and report employee salary data at the Detancio Dental clinic.